2016
DOI: 10.1039/c6cc03532a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient synthesis of functionalized α-oxyketones via Weinreb amides homologation with α-oxygenated organolithiums

Abstract: An efficient, chemoselective homologation of Weinreb amides to the corresponding variously substituted α-oxyketones has been developed via the addition of lithiated α-oxygenated species. This one-step, experimentally easy, high yielding protocol is amenable not only for accessing simple α-oxyketones but also for more complex substituted ones ranging from primary and secondary alkyl-type to aromatic ones. Full delivery of the stereochemical information contained in the starting materials is observed through bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Moreover the 3D database of compounds from synthetic source was obtained by collecting molecules belonging to different chemical classes (α-,methoxymethylketones, [20] αhalomethylketones, [21] α-cyanomethylketones, [22] α-haloamides, [23] thioamides, [24] spiroepoxyoxindoles, [25] pyrazoles, [26] dithioacetals [18b] designed and synthesized by the Pace group.…”
Section: Generation Of Three-dimensional Databasesmentioning
confidence: 99%
“…Moreover the 3D database of compounds from synthetic source was obtained by collecting molecules belonging to different chemical classes (α-,methoxymethylketones, [20] αhalomethylketones, [21] α-cyanomethylketones, [22] α-haloamides, [23] thioamides, [24] spiroepoxyoxindoles, [25] pyrazoles, [26] dithioacetals [18b] designed and synthesized by the Pace group.…”
Section: Generation Of Three-dimensional Databasesmentioning
confidence: 99%
“…Upon deprotonation of enantiopure amethyl carbamate 18 with sBuLi in CPME, as eries of a-quaternary carbonyl compounds could be prepared in excellent yields and enantiomeric ratios startingf rom the R or S carbamates (sparteinew as not required for deprotonating these chiral starting materials). The trapping with af ormyl Weinreb amide providedt he corresponding a-oxyaldehyde 19,a nd aromatic (20,21), aliphatic (22), or propargylic (23)a nalogues yieldedt he corresponding ketones.…”
Section: Resultsmentioning
confidence: 99%
“…[19] This is quite astounding because enantiomerically enriched a-substituted ketones constitute privileged frameworks across the chemical sciences. Based on our experienceo fc hemoselective acylations of a-substituted carbanions with Weinreb amides, [20] we devised an enantioand chemoselectivem ethodology to reach aw ide scope of aoxyketones and cyclic a-aminoketonesi nh igh yields, without the need for column chromatography( Scheme 1c). Furthermore,apractical method for the sustainable recovery of sol-…”
Section: Introductionmentioning
confidence: 99%
“…To overcomet he above problems,i nstead of a-halo ketones as the starting materials, Kimpee tal. [28,29] As an important extension of umpolung reactivity,w es upposed that the a-oxygenated ketones or a-thio ketonesc ould be obtained by the reactionofe lectrophilic N-alkenoxypyridinium salts and nucleophilic alcohols or thioalcohols ( Figure 1b). [25] Newman group reported that alco- [a] Prof. Dr.Z.X u, R. Zhai, T. Liang holysis of a-diazoketones under Lewis acidic conditions could afford a-alkoxyketones.…”
mentioning
confidence: 99%
“…Aryl ether alkyne substrates also afford fairly good yield of the a-ethanol ketones anda ryl chloride is tolerance (29)(30)(31). Aryl ether alkyne substrates also afford fairly good yield of the a-ethanol ketones anda ryl chloride is tolerance (29)(30)(31).…”
mentioning
confidence: 99%